The War on Our Freedoms : Civil Liberties in an Age of Terrorism - Edited by Richard C. Leone and Greg Anrig Jr. (New York BBS PublicAffairs, 2003)
Examines the consequences of the war on terrorism through the loss of civil liberties in the name of homeland security.
Keywords: Civil rights -- United States. -- September 11 Terrorist Attacks, 2001. -- War on Terrorism, 2001-2009.